Eksplorasi Ektoparasit Pada Ikan Famili Cyprinidae Di Kolam Rumah Makan Wilayah Malang Raya - Karina hanum wardany; Nia Kurniawan (Biotropika: Journal of Tropical Biology, 2014)
Ectoparasites were common found on fishes. Ectoparasites often infect parts of the fins, scales, operculum and gills in fish. This research aims to determine the types of ectoparasites on fish family Cyprinidae and the influence of environmental conditions on the number of ectoparasites. This research was conducted in three pools restaurant in Malang Raya region, then measured abiotic factors of pool water. Fish as the host of ectoparasites, taken using nets and anesthetized by using 3 phenol chloroform. Fish scales and fins were observed. Ectoparasites that attach to the parts taken and put in 70% alcohol. Ectoparasites observed and identified under a microscope. Measurement data of water quality and quantity ectoparasites were analyzed using SPSS 16 program. Argulus japonicus is a species of ectoparasite was founds in B Batu restaurant and I Dau restaurant. While ectoparasites found in G Malang restaurant was Lernaea cyprinacea. Argulus japonicus and Lernaea cyprinacea were exotic species from Japan. The entry of ectoparasites caused by introduction of Koi fish to Indonesia. The results showed that there were significant differences in the number of ectoparasites I Dau with B Batu and G Malang restaurants respectively. The correlation result between the number of ectoparasites and the physico-chemical factors were showed that the pool water DO levels were positively correlated to the number of ectoparasites.   Key word: Ectoparasites, fish family Cyprinidae, restaurant pond at Malang Area, SPSS 16